Analisis Pembentukan dan Perubahan Makna dalam Bahasa Gaul Remaja di Media Sosial Tiktok - Iin Himatul Islamiah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the phenomenon of slang usage on the TikTok social media platform as a form of linguistic adaptation in digital communication. Using a qualitative descriptive approach, this research examines how users modify language structures to create more effective, expressive, and socially meaningful interactions. Data were collected through participatory observation of content appearing on the For Your Page (FYP) feature and analyzed using textual and contextual methods. The findings reveal that slang formation on TikTok occurs within three main domains: phonological transformation through sound reduction to produce linguistic aesthetics, morphological modification through the creation of efficient acronyms, and cognitive-semantic shifts that redefine the meanings of existing vocabulary. These findings demonstrate that slang is not merely a temporary communication trend, but also functions as an important sociolinguistic instrument for constructing group identity, strengthening emotional connections, and reflecting the cognitive and cultural dynamics of contemporary digital society amid the rapid development of information technology.